PENGARUH KESADARAN, SOSIALISASI, AKUNTABILITAS PELAYANAN PUBLIK DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Wahyu Cahyadi, I Made; Jati, I Ketut (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This research aimed to determine the effect of awareness of taxpayers, dissemination taxation, accountability of public services and tax penalties on taxpayer compliance PKB in Manunggal joint office administration system under one roof (SAMSAT) Denpasar. The theory used in this research is the theory of legitimacy. The population in this research are all active CLA taxpayers registered at the Office of the Joint SAMSAT Denpasar. The samples used of 100 respondents was calculated based on the formula slovin of sampling accsidental. The data collection was conducted using non-participant observation technique and questionnaire. The data analysis technique used in this research is multiple linear regression. Based on the analysis, the taxpayer awareness, dissemination of taxation, accountability of public services and tax penalties positive effect on tax compliance in the Office of the SAMSAT PKB Denpasar.
Keywords: awareness, socialization, promoting accountability of public services, tax penalties, tax compliance